Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

suzi20

  • 4 years ago

proof: if x+y = 0, then y=-x

  • This Question is Closed
  1. hellomoto1102
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    :-??

  2. harivenuv
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    y=-x that is x=-x there for x+(-x)=0

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy